1990
DOI: 10.1105/tpc.2.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Protein Import into and Sorting inside the Chloroplast Are Independent Processes.

Abstract: Plastocyanin is a nuclear-encoded chloroplast thylakoid lumen protein that is synthesized in the cytoplasm with a large N-terminal extension (66 amino acids). Transport of plastocyanin involves two steps: import across the chloroplast envelope into the stroma, followed by transfer across the thylakoid membrane into the lumen. During transport the N-terminal extension is removed in two parts by two different processing proteases. In this study we examined the functions of the two cleaved parts, C1 and C2, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It was previously shown that pPC( 1 -67)-dihydrofolate reductase was efficiently imported into isolated pea chloroplasts in vitro but was quickly degraded in the stroma and hardly reached thylakoids (Hageman et al, 1990;America et al, 1994). This means that the transit peptide of pPC is not fully active in this fusion protein or that it is not sufficient to direct dihydrofolate reductase to the thylakoid lumen.…”
Section: Methotrexate Can Bind To and Stabilize The Dihydrofolate Redmentioning
confidence: 79%
See 1 more Smart Citation
“…It was previously shown that pPC( 1 -67)-dihydrofolate reductase was efficiently imported into isolated pea chloroplasts in vitro but was quickly degraded in the stroma and hardly reached thylakoids (Hageman et al, 1990;America et al, 1994). This means that the transit peptide of pPC is not fully active in this fusion protein or that it is not sufficient to direct dihydrofolate reductase to the thylakoid lumen.…”
Section: Methotrexate Can Bind To and Stabilize The Dihydrofolate Redmentioning
confidence: 79%
“…In the present study, we have tested a new dihydrofolate reductase fusion protein (pPC-dihydrofolate reductase) consisting of the entire plastocyanin precursor (pPC) and dihydrofolate reductase for its ability to move across the thylakoid membrane. In contrast to pPC( 1 -67)-dihydrofolate reductase, which ends up in the stroma during in vitro import (Hageman et al, 1990;America et al, 1994), pPCdihydrofolate reductase could reach the thylakoid lumen after being imported into chloroplasts. pPC-dihydrofolate reductase therefore allowed us, for the first time, to compare directly the effects of methotrexate on the translocation of the passenger dihydrofolate reductase moiety across the thylakoid membrane with that across the envelope membranes.…”
mentioning
confidence: 98%
“…The dihydrofolate reductase (DHFR) cDNA was excised from the plasmid PC-DHFR (Hageman et al, 1990) and subcloned into the BamHl and Hindlll sites of pBluescript SK+. A linker, made of two oligonucleotides with the sequences 5'-CTAGAATCGAAGGTCGTG-3' and 5'-GATCCACGACCTTCGATT-3', which contains Xbal, factor Xa, and BamHl restriction sites, was then inserted into the Xbal and BamHl sites of the plasmid.…”
Section: Chimeric Constructs Encoding Fusion Proteinsmentioning
confidence: 99%
“…They are imported by a process that involves binding to receptors on the plastid surface, ATP-dependent transport across the plastid envelope, proteolytic removal of the transit peptide, and assembly into functional structures. Assembly can involve further transport into or across the, thylakoid membrane (Cline, 1986;.Hageman et al, 1990;Payan and Cline, In this paper, we address the possibility that the activity of the import apparatus is also regulated during chloroplast development. Our experimental approach involved isolating plastids from developing wheat leaves and analyzing 1991).…”
Section: Introductionmentioning
confidence: 99%